Growth Response of Mustard Green (Brassica juncea L.) Because of Giving Cow Compost and Mycorrhiza Fertilizer Dosages - Fatimah, Sati; Ikhwan, Ali; Muhidin; machmudi; Ishartati, Erny (Universitas Muhammadiyah Malang, 2024)
Mustard green (Brassica juncea L.) is a leafy vegetable with a subtropical climate, but this plant can adapt well to tropical climates that it suitable to be planted and grow in Indonesia. The formulation of problem in this study is to lessen the use of chemistry fertilizer in fertilization on plants, especially mustard green (Brassica juncea L.). This study aims to review the growth response of mustard green (Brassica juncea L.) because of the dosage of cow compost and mycorrhiza fertilizer dosages. This study used a randomized block design (RBD) arranged in a split plot with 2 factors. The first factor as main block of cow compost dosage consists of three levels, they are 2,5 tons/ha, 5 tons/ha, and 10 tons/ha. The second factor is offspring block, a mycorrhiza dosage consisting of three levels: 1 tablet/plant, 2 tablets/plant, and 3 tablet/plant, each repeated 3 times. Observed variables are plant height, the number of leaves, leaf wide, fresh weight and dried weight of the plant, fresh and dried weight, fresh and dried ratio of root weight, and dried crown weight. The result of this study shows that there is no interaction between giving cow compost and mycorrhiza dosage toward mustard green height, fresh weight and dried weight, fresh and dried ratio of root weight and dried crown weight, but separately dosing cow manure 2.5 ton/ha can increase broad leaf mustard plants at 2 weeks after planting and dosage, as well as mycorrhiza 1 tablet/plants and 2 tablets/plant, has been able to increase leaf area from age 2 weeks after planting.